Pengaruh Terpaan Tayangan Review Gadget Di Youtube Terhadap Minat Beli Anggota Komunitas Game @Freefireriau - Ikhsan, Muhammad; Daherman, Yudi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
This study aims to see the big influence of exposure to gadget reviews on buying interest in the @Freefireriau game community members. Gadget review is a video review content about gadgets, in which the reviewer will review gadget products which are then uploaded to YouTube. This study uses the theory of SOR (Stimulus-Organism-Response) with the assumption that the message conveyed is a response or motivation which can carry out a change in attitude behavior where the form of behavior change here is buying interest. In this study, the research method used was quantitative with a sample of 85 people using non-probability sampling using purposive sampling technique. By using a questionnaire as an instrument which was then processed using the SPSS 25 program. The validity test of the instrument was carried out using Correlation Product Moment and further Reliability Test with Alpha Cronbach, for analysis using the Simple Linear Regression Test. The results show that the Gadget Review Exposure to Buying Interest of @Freefireriau Game Community Members has a significant effect. With the results of the coefficient of determination, the R value is 0.696, which indicates that it is in the strong category and the R Square value (R2) is 0.484 or indicates that the effect of Gadget Review Exposure on Purchase Intention is 48.4% which is included in the medium category, and for the rest it is 51.6 % findings by other factors not present in this study.